Alkohol: Definisi, Pengharaman, Metabolisme Dan Kegunaannya - Latipah Mohd Noor; Siti Rubaini Mat; Norhakimah Dhiauddin; Afif Arifin (USIM Press, 2024)
Vol. 23 (2018): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [April 2018]